Self-Esteem and Social Comparison as a Predictor of Body Image in Adolescent Girls - Resha Resha; Rita Eka Izzaty (Green Publisher Indonesia, 2025)
Body image concerns represent a significant mental health challenge among contemporary adolescent populations, particularly for girls navigating developmental transitions and sociocultural pressures related to physical appearance. The increasing prevalence of body dissatisfaction among youth has been associated with various psychological difficulties, including depression, anxiety, eating disorders, and diminished self-esteem, underscoring the urgency of understanding the factors that shape body image perceptions during this critical developmental period. This study aims to determine the extent to which self-esteem and social comparison can predict body image in adolescent girls. This research employed a quantitative approach using a correlational design. The subjects consisted of 100 female adolescents aged 16–21 years, located in Yogyakarta. The sampling technique used was cluster random sampling. Data were collected using questionnaires, namely the Rosenberg Self-Esteem Scale (RSES), the Iowa–Netherlands Comparison Orientation Measure (INCOM), and the Positive Body Image Adolescent Scale (PBIAS), all of which were adapted into Indonesian. Reliability testing used Cronbach’s Alpha, producing reliability coefficient values of 0.875, 0.857, and 0.950, respectively. Data analysis was performed using multiple linear regression with IBM SPSS version 26. The results showed that the hypothesis was accepted, with R = 0.642, R² = 0.412, and a significance value of 0.000 (<0.05). Therefore, self-esteem and social comparison have a positive and significant effect on body image in adolescent girls. This indicates that self-esteem and social comparison can predict body image in teenage girls by 41.2%, while other factors account for the remaining 58.8%.